Development of Entrepreneurship’s Ethics from Islamic Perspective - Abdul Hamid, Solahuddin; Othman, Azizah; Hanapi, Mohd Shukri (Human Resource Management Academic Research Society, 2019)
Scholars across the world are said to be in agreement that a successful entrepreneur should be an all- round individual who can adapt to different environment be they cultural or geographical. For instances, one needs to first be knowledgeable about the products and their market. One must also have the discipline and be confidence, passionate, ambitious and liberal. It is also always important to build a strong professional network with people of the same as well as different market. For those inexperienced, possessing such knowledge and skills will definitely enable one to succeed should he or she ventures into the field. Nevertheless, it is important to note that an entrepreneurship is not solely for profitable cause or trading. It is also considered as a social community service which has the potential to build a civilisation and to sustain its future. When a work is done based on Islamic values, both mind and action must be in accordance and holistically based. In other words, a Muslim entrepreneur is not only defined as possessing the knowledge and skills mentioned, but also the integration with the teachings of Islam